Techno-economic and environmental analysis of methanol and dimethyl ether production from syngas in a kraft pulp process. (July 2022) - Ribeiro Domingos, Meire Ellen Gorete; Flórez-Orrego, Daniel; Teles dos Santos, Moisés; de Oliveira, Silvio; Maréchal, François
Highlights: The exergy efficiencies of the conventional scenario and the integrated plants average 40% and 45%, respectively. The overall CO2 emission balances of the conventional scenario and the integrated plants vary from 1.97 to -0.07 tCO2 /tPulp, respectively. A utility optimization tool is integrated to the main simulation model. Interest rate, carbon taxes and prices influence are analysed using different scenarios. Inefficiencies and impacts of energy supply chains are considered. Abstract: The conventional configuration of a pulp mill, in which black liquor is concentrated and burnt, is compared to the upgrading gasification routes for methanol (MeOH) or dimethyl ether (DME) co-production. To this end, various exergy-based and environmental impact indicators are assessed in the light of different utility supply scenarios. The combined exergy and energy integration analysis are used to identify potential improvements related to the decarbonization and mitigation of the process irreversibility. As a result, the exergy efficiencies of the conventional scenario and the integrated plants average 40% and 45%, respectively, whereas the overall CO2 emission balances vary from 1.97 to -0.07 tCO2 /tPulp, respectively. Additionally, an incremental economic analysis that envisages future carbon taxation scenarios suggests that only MeOH or DME co-production routes with partial electricity import may economically outperform the conventional kraft pulp mill for moderate carbon taxations. These results highlight the relevance of the electricity import from the Brazilian mix for pushing upwards the share of renewable energy resources in the production of traditionally fossil-based fuels and chemicals.